PENERAPAN APLIKASI BAMBOOZLE UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS BELAJAR SISWA DI SB SUNGAI BULOH MALAYSIA - Anggara, Bayu; Heriyana, Tio; Hermawan; hadiana, oman; Astria Nur, Hana (Jurnal PGSD, 2025)
Abstract The learning process carried out with various media to achieve the goals of an effective and efficient learning process is not always suitable, the cause is usually due to learning habits, lack of interest and understanding of students, there are several factors for student failure in achieving effective and efficient learning goals including internal factors that usually come from the students themselves, such as poor understanding of the material, lack of motivation, external factors usually come from outside the students such as the learning environment, family, and lack of use of learning media. Based on observations of teachers during the learning process, it shows that student activity in the learning process during learning is low and passive, students only receive material, lack of interest in paying attention to the material presented by the teacher, students are less brave in expressing their opinions, so that student understanding is very minimal in mathematics learning material. Good learning construction is if the learning is carried out centered on students. Therefore, as a solution to the problems in this study, the author applies the Bamboozle application, where students' understanding of learning focuses on students who work on or understand the material through the Bamboozle application. As well as for evaluation of assessments and to find out the extent to which students understand the learning material and show their interest in the learning material provided and increased learning outcomes. The results of the research from the implementation of the Bamboozle Application have the final results of the calculation of the hypothesis test (t-test) are known to have an average posttest result of 83.33 while the pretest value is 68.33 so that it is known that the posttest learning outcome score is greater than the pretest. It is also known that the Tcount value is 2.247, the Ttable value is 2.179. So it can be concluded that Tcount> Ttable (2.247> 2.179) and the significance value is less than 0.05 (p = 0.000 <0.05), so it can be stated that there is a significant difference in increasing mathematical understanding and a significant increase in learning outcomes in the Pretest and posttest values. Thus it can be concluded that H0 is rejected and Ha is accepted. Keywords: Learning, Mathematical Understanding, Bamboozle Application